The Effects of Marital Status and Children on Savings and Portfolio Choice - Love, David A. (Review of Financial Studies, 2010)
This paper investigates the impact of demographic shocks on optimal decisions about saving, life insurance, and, most centrally, asset allocation. The analysis indicates that marital-status transitions can have important effects on optimal household decisions, particularly in the cases of widowhood and divorce. Children also play a fundamental role in portfolio choice; in addition to leading to substantially different average allocations, they also have strong interaction effects with changes in marital status. Panel data evidence on stockholding suggests that changes in marital status and children matter empirically as well, but not always in the manner that the model predicts. The Author 2009. Published by Oxford University Press on behalf of The Society for Financial Studies. All rights reserved. For Permissions, please e-mail: journals.permissions@oxfordjournals.org., Oxford University Press.